2015
DOI: 10.1080/15421406.2015.1031999
|View full text |Cite
|
Sign up to set email alerts
|

Control of Laser Speckle Noise by Using Polymer-Dispersed LC

Abstract: JapanLaser speckle noise occurs owing to the strong interference that originates in the high coherency of laser light and the surface topography of screen. The suppression of the speckle noise is necessary for laser displays such as an image projection system. To reduce the speckle noise, we have tried to control the speckle pattern by using liquid crystals (LCs). In this paper, we offer an idea for suppressing the speckle noise using a polymer-dispersed LC (PDLC) cell in which the speckle pattern can be varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…11 They later reported 25% speckle reduction with an electrically addressed polymer-dispersed nematic LC device. 12 Similarly, Andreev et al have reported 50% speckle reduction with the application of more complicated waveforms to a ferroelectric LC. 13,14 The practicality of these devices is limited by their use of a polarizer and complicated waveforms.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…11 They later reported 25% speckle reduction with an electrically addressed polymer-dispersed nematic LC device. 12 Similarly, Andreev et al have reported 50% speckle reduction with the application of more complicated waveforms to a ferroelectric LC. 13,14 The practicality of these devices is limited by their use of a polarizer and complicated waveforms.…”
mentioning
confidence: 99%
“…[11][12][13][14] For example, Furue et al achieved 40% speckle reduction by applying an alternating squarewave electric field to a ferroelectric LC, combined with a wedge cell and polarizer. 11 They later reported 25% speckle reduction with an electrically addressed polymer-dispersed nematic LC device.…”
mentioning
confidence: 99%
“…To date, there have been numerous reports demonstrating speckle reduction using LC devices and materials. For example, previous studies have shown a reduction in the speckle contrast using: (1) a nematic LC with photo-isomerisable alignment layer that enables two orthogonal polarisation states to be created thereby leading to polarisation diversity 15 ; (2) a chiral smectic ferroelectric LC (FLC) with an alternating field applied that creates a spatially and temporally random refractive index across the cell 16 18 ; (3) surface and/or polymer stabilised FLC 19 for polarisation diversity; (4) nematic LCs mixed with photocurable monomers for light scattering 20 , and (5) the use of a LC spatial light modulator (SLM) that applies multiple random phase masks corresponding to the Hadamard orthogonal function to create statistically independent speckle patterns at the observer 21 . These techniques, whilst they show promise, are not without their limitations such as a small amount of speckle reduction, complex electric field profiles, and/or the use of expensive and bulky components (such as an SLM).…”
Section: Introductionmentioning
confidence: 99%
“…By virtue of their electro‐optic properties, liquid crystals (LCs) are appealing for the reduction of the speckle contrast and as a result have been considered for this purpose by numerous research teams. [ 6–15 ] An example of previous research in this area involved the use of a nematic LC device with a controllable alignment layer consisting of polyvinyl alcohol (PVA) and an azo dye. [ 6 ] Exposing the device to ultraviolet (UV) light resulted in a reorientation of the LC director through the PVA/azo dye alignment layer enabling access to two orthogonal polarization states and thus giving rise to a reduction in the speckle contrast of 1 / 2 .…”
Section: Introductionmentioning
confidence: 99%
“…have also reported speckle reduction using FLCs that are either surface or polymer stabilized as well as the use of nematic LCs dispersed with a photocurable monomer. [ 10,11,13 ] Other techniques have included the addition of nanoparticles to LC materials. [ 14,15 ] Alternatively, LC spatial light modulator (SLM) technology has been used to generate multiple random phase masks corresponding to the Hadamard orthogonal functions.…”
Section: Introductionmentioning
confidence: 99%